Essays in honor of M. Hashem Pesaran : prediction and macro modeling - Chudik, Alexander; Hsiao, Cheng; Timmermann, Allan (Advances in econometrics ;, 2022)
The collection in Volume 43 Part A of Advances in Econometrics serves as a tribute to Professor M. Hashem Pesaran. Hashem is one of the most innovative, influential, and productive econometricians of his generation, with over 200 papers published in leading scientific journals to his credit along with highly influential books on both theoretical and applied topics, significantly pushing forward the frontiers of knowledge in econometrics and economics. Thanks to his profound and pioneering work on theoretical and empirical questions, the economics profession has gained a much better understanding of both the power and limitations of econometric analysis. Consistent with Hashem's contributions, this volume comprises of chapters on a variety of topics covering prediction and macroeconomic modelling. The list of topics includes studies on Bayesian Quantile regression methods, forecasting implications from the economic impact of global warming, assessment of DSGE models, and parameter estimation in the presence of multiple breaks.